Primeros pasos de un estudio sobre literatura de tradición oral en Baja Navarra - Larralde, Alexandra (Huarte de San Juan. Filología y Didáctica de la Lengua, 2016)
With the opportunity of an immersion in the Archive of the Intangible Heritage of Navarre, we’ll be dedicated to prepare and bring up to date the inventory of its intangible heritage, and more exactly of the oral tradition in the culture of Nafarroa Behera. This kind of heritage gets together different genders of popular narrations as tales, myths, legends, songs, riddles, proverbs. This vast field of studies will make us rediscover the works of passed century’s folklorists, with their first collections of oral traditions. Moreover, through fieldwork, it will conduce to the perception of different aspects of the popular imaginary, with its evolutions up to now. Finally, the aim will be to highlight the cultural unity beyond artificial frontiers and historical events which set appart the two provinces, Upper Navarre and Lower Navarre, so linked in the past.
Keywords: Lower Navarre (Baja Navarra); intangible cultural heritage; folk literature; corpus; field work